2005
DOI: 10.1111/j.1540-8167.2005.40531.x
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial and Three‐Dimensional Mapping of Spontaneous Atrial Arrhythmias in Patients with Refractory Atrial Fibrillation

Abstract: Simultaneous biatrial and NCM permits successful AF mapping in different AF populations and demonstrates a biatrial spectrum of spontaneous triggers and tachycardias. Organized monomorphic tachycardias with multiple unilateral or biatrial locations are commonly observed in human AF. Patients with heart disease or persistent AF have a more extensive distribution as well as simultaneous coexistence of multiple tachycardias during AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Consistent with these observations, detailed mapping in AF patients showed that organized monomorphic AFL commonly occurred before paroxysmal AF. 20 In addition, the regional distribution of organized monomorphic atrial arrhythmias was more extensive in patients with structural heart disease and persistent AF compared with patients without structural heart disease or paroxysmal AF. 20 Therefore, these results support the clinical observation that AFL is induced preferably by focal discharges for a normal spatial dispersion of atrial refractoriness, whereas AF is more likely to be induced when the dispersion is increased, 21 such as due to atrial inflammation or structural heart diseases.…”
Section: L-type Ca 2؉ Current and Restitution Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with these observations, detailed mapping in AF patients showed that organized monomorphic AFL commonly occurred before paroxysmal AF. 20 In addition, the regional distribution of organized monomorphic atrial arrhythmias was more extensive in patients with structural heart disease and persistent AF compared with patients without structural heart disease or paroxysmal AF. 20 Therefore, these results support the clinical observation that AFL is induced preferably by focal discharges for a normal spatial dispersion of atrial refractoriness, whereas AF is more likely to be induced when the dispersion is increased, 21 such as due to atrial inflammation or structural heart diseases.…”
Section: L-type Ca 2؉ Current and Restitution Propertiesmentioning
confidence: 98%
“…This is consistent with a detailed mapping study that showed that organized monomorphic atrial tachyarrhythmias induced by premature beats could first arise from the RA, interatrial region, or LA in patients with AF. 20 Moreover, for ectopic foci in the RA, especially those closer to the sinoatrial node such as the superior vena cava and crista terminalis, the size of the vulnerable window for the induction of AFL/AF became markedly smaller than that of the PV ectopic foci ( Figure 4B). The effect of increasing vulnerable window size when increasing the distance between 2 pacing sites (in this case sinoatrial node and ectopic focus) has been attributed to a physical principle known as symmetry breaking, 10,14 as described in Dynamic Repolarization Dispersion and Conduction Block in Results.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…These data are in agreement with the different frequency gradients, 43 and spatiotemporal organization in paroxysmal AF patients compared with persistent AF patients. 44 Parasympathetic signaling is altered in human atrial myocytes obtained from chronic AF patients. Data indicate that the short APD and reduced APD response to changes in activation frequency that characterize chronic AF correlated with reduced I Ca-L and increased I K1 and I K,ACh .…”
Section: Electrical and Structural Remodeling And Rotorsmentioning
confidence: 99%
“…Today, debate centers on the DANISH trial challenging defibrillator benefits in a large segment of the ventricular dysfunction population [1]. Biatrial mapping in atrial fibrillation performed by a few groups two decades ago suggested biatrial triggers and tachycardias that had been in disfavor for this epoch, now have returned to center stage with new mapping technology [2][3][4]. This has initiated a major pendulum swing in ablation therapy beyond the pulmonary vein triggers and tachycardias.…”
mentioning
confidence: 99%